Calculation of induced currents during the inductional heating by a flat rectangular multiturn solenoid - Gnatov, A.; Chaplyhin, Ye. O.; Sabokar, O. S; Trishkyn, Ye. V; Гнатов, А. В.; Чаплыгин, Е. А; Сабокар, О. С.; Тришкин, Е. В.; Чаплигін, Е. А.; Трішкин, Е. В. (Харківський національний автомобільно-дорожній університет, 2016)
The analysis of electromagnetic processes and calculation of the induced currents in the system for the induction heating, presented by the flat rectangular multiturn solenoid placed above the plane of the thin-walled sheet-metal has been carried out. Graphic dependences for spatial distribution of the induced currents and coefficient of transformation of current in the area under inductor have been built. The nature of the excitation system has been determined to have no effect on the output characteristics of the induction heating.
Расчет индуцированных токов при индукционном нагреве плоским прямоугольным многовитковым соленоидом
Розрахунок індукованих струмів при індукційному нагріві плоским прямокутним багатовитковим соленоїдом
Keywords: induction heating; inductor system; induced current; electromagnetic processes; eddy currents; heating of metal; индукционный нагрев; индукторная система; индуцированный ток; электромагнитные процессы; вихревые токи; нагрев металла; індукційний нагрів; індукторна система; індукований струм; електромагнітні процеси; вихрові струми; нагрів металу; 621.318.4